When You Can't Walk a Mile: Walking Limitation Prevalence and Associations Among Middle‐Aged and Older US Adults with Arthritis: A Cross‐Sectional, Population‐Based Study. Issue 6 (24th July 2019) - Theis, K. A.; Murphy, L. B.; Baker, N. A.; Hootman, J. M.
Abstract : Objective: We examined walking limitations and associated characteristics among middle‐aged and older US adults with arthritis, overall, and by sex. Methods: Using 2005‐2006 Arthritis Conditions and Health Effects Survey (ACHES) data (n = 1793), we estimated "a lot" and "any" ("a lot" or "a little" combined) walking limitation for more than 1 mile (1.6 km) among US adults 45 years or older with arthritis and examined associations (sociodemographics, arthritis symptoms and effects, psychosocial measures, and physical health) with walking limitations in unadjusted and multivariable (MV) adjusted logistic regression models using prevalence ratios (PRs) and 95% confidence intervals, accounting for the complex survey design. Results: Respondents frequently reported "a lot" (48%) and "any" (72%) limitation for more than 1 mile. Women reported higher prevalence of all levels of walking limitation versus men (eg, 51% vs 42% for "a lot" overall); additionally, the gap for walking limitations between women and men widened with age. Limitation was high for both sexes at all ages, affecting 1‐in‐3 to 4‐in‐5, depending on level of walking limitation. The strongest MV associations for "a lot" of walking limitation among all respondents included substantial and modest arthritis‐attributable life interference (PR = 2.5 and 1.6, respectively), age 75 years or older (PR = 1.5), and physical inactivity and fair/poor self‐rated health (PR = 1.4 for both). Conclusion: Walking limitations among middle‐aged and older adults are substantial. Existing proven interventions that improve walking ability and physical function may help this population to reduce and delay disability.